Designer Microorganisms for Optimized Redox Cascade Reactions – Challenges and Future Perspectives. Issue 8 (15th May 2015) - Bayer, Thomas; Milker, Sofia; Wiesinger, Thomas; Rudroff, Florian; Mihovilovic, Marko. D.
Abstract: An immense number of chemical reactions are carried out simultaneously in living cells. Nature's optimization approach encompasses the assembly of reactions in cascades and to embed them in finely tuned metabolic networks. With the vast progress in the field of biocatalysis, man‐made cascades, especially redox cascades, have reached a degree of complexity that needs tools for improved control and optimization. Combined strategies from biocatalysis, metabolic engineering and synthetic biology lead to the establishment of artificial metabolic pathways with minimized interference with the cellular host environment. This review will focus on genetic and metabolic engineering tools for the assembly and introduction of de novo redox pathways into the host Escherichia coli and will present state of the art redox cascades performed by tailor‐made microbial cell factories. Abstract :